Abuso sexual y su repercusión en la salud mental de un adolescente de 16 años de la ciudad de Milagro - Jubilez Chacon, Maria Elena (2022)
This case study is focused on sexual abuse and its impact on the mental health of a 16-year-old adolescent from the city of Milagro. Following the line of research: prevention, diagnosis, evaluation and psychotherapeutic treatment in the clinical setting, which at the same time is linked to the subline of research: individual and/or group psychotherapy. The abuse severely affected the mental health of the individual in question. In addition to the fact that there were several warning indicators that showed the good or bad mental health that the victim was having, as these were reflected in the patient's behavior when relating to others and interacting with his environment in daily life, also these acts brought with them long term sequelae that undoubtedly will hinder the subject's life. In the case study, important data were collected for the progress of the research and its respective elaboration; psychometric techniques and tools were applied, such as the Beck Depression Inventory (BDI-2) with a score of 27, which is in the range of moderate depressive episode; the Hamilton test for anxiety, which yielded the following results: anxiety was shown in the psychic area of 14, and with somatic anxiety of 10, a total of 24, which is considered as severe anxiety; according to the information collected during the sessions and the psychometric batteries used and according to the diagnostic criteria of DSM-5, the patient meets the criteria for generalized anxiety disorder 300. 02 and ICD-10 (F41.1) and Moderate depressive episode 296.22 and ICD-10 (F31.2).